Why and How Physical Activity Promotes Experience-Induced Brain Plasticity - Kempermann, Gerd; Fabel, Klaus; Ehninger, Dan; Babu, Harish; Leal-Galicia, Perla; Garthe, Alexander; Wolf, Susanne (Frontiers in Neuroscience, 2010)
Adult hippocampal neurogenesis is an unusual case of brain plasticity, since new neurons (and not just neurites and synapses) are added to the network in an activity-dependent way. At the behavioral level the plasticity-inducing stimuli include both physical and cognitive activity. In reductionistic animal studies these types of activity can be studied separately in paradigms like voluntary wheel running and environmental enrichment. In both of these, adult neurogenesis is increased but the net effect is primarily due to different mechanisms at the cellular level. Locomotion appears to stimulate the precursor cells, from which adult neurogenesis originates, to increased proliferation and maintenance over time, whereas environmental enrichment, as well as learning, predominantly promotes survival of immature neurons, that is the progeny of the proliferating precursor cells. Surprisingly, these effects are additive: boosting the potential for adult neurogenesis by physical activity increases the recruitment of cells following cognitive stimulation in an enriched environment. Why is that? We argue that locomotion actually serves as an intrinsic feedback mechanism, signaling to the brain, including its neural precursor cells, that the likelihood of cognitive challenges increases. In the wild (other than in front of a TV), no separation of physical and cognitive activity occurs. Physical activity might thus be much more than a generally healthy garnish to leading “an active life” but an evolutionarily fundamental aspect of “activity”, which is needed to provide the brain and its systems of plastic adaptation with the appropriate regulatory input and feedback.